Conversações hipervisuais: vamos falar sobre olhares masculinizados? - Ospina Álvarez, Juan Sebastián (2018)
The present thesis intercrosses the visual cultures studies and the gender studies, having as object of analysis six encounters which made up the NarrATIVIDADES extension project. Genders Lab and narratives, which happened in November and December 2015, March and April 2017, in addition to the narratives produced by the people who committed themselves to the registered design from the School of Visual Arts (FAV) at the Pro-rector of Extension and Culture (PROEC) from the Federal University of Goiás (UFG). Masculinities in this study are treated as cultural constructs that are supported by the variety of speeches to operate in societies. For this reason, after reports of several visualities are problematized, these constructs of discipline and control that not only relate to the scope of the affective-sexual, but also to the domain of symbolic production. In this sense, this research craved analyze the possibilities and deconstruction strategies of visualities on masculinities and masculinization of looks, this from hypervisuals talks, works with memories and narratives produced by the group of students and teachers on the main subject of research: objectification and women hypersexualization, especially black women and black men; invisibility of the non heteronormative identities and androcentrism in using audiovisuals and media devices. The methodological approach nicknamed and used in this process corresponds to the hypervisual conversations that consist in an expansion of a narrative research expansion from works with visualities and countervisualities. To better comprehend the proper use of the term ‘hypervisuals’ are threshed, throughout the text, discussions around the concept of visual, visual images, the visualities, the countervisualities, the scopic regimes and many other terms of the studies of visual cultures. Since it’s a study linked to the Line of Image Cultural Research of image and Mediation Processes, this research outlines also the use of hypervisual narratives as possible to develop pedagogical processes with deconstructivist bias.